2017
DOI: 10.1038/s41598-017-02880-0
|View full text |Cite
|
Sign up to set email alerts
|

Gut Dysbiosis and Neurobehavioral Alterations in Rats Exposed to Silver Nanoparticles

Abstract: Due to their antimicrobial properties, silver nanoparticles (AgNPs) are being used in non-edible and edible consumer products. It is not clear though if exposure to these chemicals can exert toxic effects on the host and gut microbiome. Conflicting studies have been reported on whether AgNPs result in gut dysbiosis and other changes within the host. We sought to examine whether exposure of Sprague-Dawley male rats for two weeks to different shapes of AgNPs, cube (AgNC) and sphere (AgNS) affects gut microbiota,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(77 citation statements)
references
References 93 publications
1
71
1
3
Order By: Relevance
“…33 Rats receiving a daily administration of 3.6 mg kg −1 by gavage of cubic or spherical Ag NPs (20 mL kg −1 body weight) for 14 days also showed no evidence of histological disturbance to the stomach, small intestine, cecum or colon. 34 Exposure to dissolved silver via the water is known to interfere with branchial sodium homeostasis in trout. 35 However, dietary silver generally does not.…”
Section: Growth Gut Health and Sub-lethal Effectsmentioning
confidence: 99%
“…33 Rats receiving a daily administration of 3.6 mg kg −1 by gavage of cubic or spherical Ag NPs (20 mL kg −1 body weight) for 14 days also showed no evidence of histological disturbance to the stomach, small intestine, cecum or colon. 34 Exposure to dissolved silver via the water is known to interfere with branchial sodium homeostasis in trout. 35 However, dietary silver generally does not.…”
Section: Growth Gut Health and Sub-lethal Effectsmentioning
confidence: 99%
“…It is generally accepted that silver nanoparticles, as well as many other engineered nanoparticles alter the human and animal microbiota. This alteration is mostly associated with dysfunctions which are correlated with the size and shape of the silver nanoparticles (AgNC -silver nanocubes and AgNSsilver nanospheres) [132][133][134][135][136]. Considering the most representative species of the microbiota it was found that Clostridium spp., Bacteroides uniformis, Christensenellaceae, and Coprococcuseutactus were decreased in AgNC exposed group, whereas, Oscillospira spp., Dehalobacterium spp., Peptococcaeceae, Corynebacterium spp., Aggregatibacterpneumotropica were reduced in AgNS exposed group.…”
Section: Toxicity and Challengesmentioning
confidence: 99%
“…It is generally accepted that silver nanoparticles, as well as many other engineered nanoparticles alter the human and animal microbiota. This alteration is mostly associated with dysfunctions which are correlated with the size and shape of the silver nanoparticles (AgNC -silver nanocubes and AgNSsilver nanospheres) [130][131][132][133][134]. Considering the most representative species of the microbiota it was found that Clostridium spp., Bacteroides uniformis, Christensenellaceae, and Coprococcuseutactus were decreased in AgNC exposed group, whereas, Oscillospira spp., Dehalobacterium spp., Peptococcaeceae, Corynebacterium spp., Aggregatibacterpneumotropica were reduced in AgNS exposed group.…”
Section: Toxicity and Challengesmentioning
confidence: 99%